Estudo da resposta imune celular de indivíduos residentes em área endêmica para leishmaniose tegumentar americana (LTA) - Ariane Baratta Masini (2006)
In this study, we evaluated the immune mechanisms associated to establishment of human cutaneous leishmaniasis, studying the immune response of infected individuals with different times of lesion development. Our results shows, that early in the infection, there is a predominance of type 2 immune response, associated with leihmania growth and disease progretion.However this is a transitory phenomenon, since patients with older lesions shows a predominat type 1 immune profile, associated to macrophage activation, and leishmania killing. It is weel know that the synthesis of regulatory cytokines are important for the modulation of the type 1 exacerbated immune response and that this modulatory activity is pivotal for the maintenance of tissue integrity in the host. In this context a positive correlation between LSA specific IFN-γ production and the number of IL-10 producet T-lymphocytes in these patients was demonstrated. Our second objective, was evaluated the immune mechanisms associated to control and resistance in human cutaneous leishmaniasis. For this study, we evaluated cured individuals, treated with chemotherapy (Q) and immunochemotherapy (IQ), and endemic non-infected individuals with negative Montenegro skin test without history of lesion (TM). We observed in cured individuals, in innate immunity cells, na increase in the synthesis of type 1 cytokines, and a decrease in the synthesis of IL-4 and IL-10. When we evaluated the T lymphocytes, and subpopulations TCD4+ and TCD8+, we observed in Q group a decrease in the synthesis of type 2 cytokines, and in IQ individuals, a decrease in type 2 cytokines and a increase in type 1 cytokines. In the IQ group, we also observed na increase in nitrate plus nitrite plasmatic levels. This response can explain the use of this association in HIV/leishmania co-infected patients. When we evaluated the TM group, we observed a distinct immune profile. In yhese patients, the neutrophils are important source of IL-4, but, in these individuals, this cytokines is associated with na increase in macrophage CD23 expression, and a high IFN-γ/IL-10 ratiois observed, as well as elevated nitrite plus nitrate plasma levels, suggesting that in these individuals, the basal levels of IFN-γ and TNF-α are sufficient to control parasite growth without inducing pathology and consequently lesion development.